PENGARUH SALES GROWTH, KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK (Studi Empiris Pada Perusahaan Sektor Industrials yang terdaftar di Bursa Efek Indonesia Tahun 2020 - 2024): AGRESIVITAS PAJAK - Intan Nuraini; Muhammad Rizal Saragih (JEKOS (Jurnal Ekonomi Dan Sosial), 2026)
This study aims to determine the effect of sales growth, financial performance, and company size on tax aggressiveness in industrial sector companies listed on the Indonesia Stock Exchange (IDX). This is a quantitative study. The data used in this study are secondary data in the form of annual financial reports and annual reports of industrial sector companies for the years 2020-2024, downloaded through searches on the official Indonesia Stock Exchange website and the official websites of the companies used as samples. The study population was 65 industrial sector companies listed on the Indonesia Stock Exchange for the years 2020-2024. A sample of 14 companies was selected using purposive sampling. Testing was conducted using multiple linear regression analysis using E-Views version 12. The results of the data processing for simultaneous hypothesis testing (F-test) indicate that sales growth, financial performance, and company size jointly influence tax aggressiveness. The results (t-test) indicate that sales growth has no effect on tax aggressiveness. Financial performance does influence tax aggressiveness. Company size does not influence tax aggressiveness.   Keywords: sales growth, financial performance, company size, tax aggressiveness.